COMPARISON OF SURGICAL SITE INFECTION BETWEEN DIABETIC AND NON-DIABETIC PATIENTS IN CLEAN SURGICAL PROCEDURES - RAJA , RA; ABBASI , MH; TAJ , MRU; TALHA, .; QAYYUM , T (Biological and Clinical Sciences Research Journal, 2024)
Surgical site infections (SSIs) are a major concern in healthcare, especially for individuals with diabetes. Diabetes can impair wound healing and weaken the immune system, increasing the risk of SSIs. Studying SSIs in diabetic versus non-diabetic patients undergoing clean surgeries is vital for improving patient care. Objective: The primary objective of this study was to investigate the incidence of surgical site infections (SSIs) in individuals with diabetes compared to those without diabetes who underwent clean surgical procedures. Methods: After the ethical approval from the institutional review board, this comparative study was conducted at Combined Military Hospital Jhelum from July 2022 to December 2023. A consisted of people with diabetes (n=50), while Group B comprised patients who did not have diabetes (n=50). All patients were administered suitable antibiotics before surgery. Each patient received a singular intravenous dose of Ceftriaxone 1g, administered thirty minutes before initiating the initial incision. The patients were monitored for surgical site infections (SSI), defined as the presence of redness, fever, tenderness at the incision site, discharge from the surgical wound, or the development of an abscess within 28 days after surgery. Results: Most participants in both study groups underwent open ventral hernia repair procedures, 54% in group A and 58% in group B. Mean± S. D of the Hb1Ac levels of the participants in both groups was 8.46±1.16 and 4.14±1.01 (P=<0.0001). 58% of participants in Group A, while 22% in Group B had surgery-associated complications (p<0.0001). 30% of participants in Group A, while 10% in Group B had SSI (p<0.0001). Conclusion: Individuals with diabetes are more susceptible to experiencing higher rates of surgical site infection, especially in cases of procedures that are considered clean, in comparison to individuals without diabetes.